2017
DOI: 10.1108/k-05-2016-0107
|View full text |Cite
|
Sign up to set email alerts
|

The OWA distance operator and its application in business failure

Abstract: Purpose The purpose of this paper is to develop a goodness index based on Hamming distance and ordered weighted averaging distance (OWAD), which is useful to make decisions. These alternative measures enrich the results of diagnostic fuzzy models and facilitate the experts’ task in decision-making. An application to a set of firms to verify the results is also presented. Design/methodology/approach The paper follows the basis of OWA operators to design a methodology to reduce the map of causes of business fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Regarding the authors, we observed little connection between them. For instance, Scherger et al (2017) published two of the articles, and Terceño et al (2018) is the main author of one of the papers and is present as a co-author in two others. The other authors did not demonstrate connections between their studies.…”
Section: Analysis and Interpretation Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the authors, we observed little connection between them. For instance, Scherger et al (2017) published two of the articles, and Terceño et al (2018) is the main author of one of the papers and is present as a co-author in two others. The other authors did not demonstrate connections between their studies.…”
Section: Analysis and Interpretation Of The Resultsmentioning
confidence: 99%
“…In this integrative review, which covered the last ten years, we found that the issue of vulnerability or business failure was little addressed in the literature during the ten years, considering the small number of articles published on the subject. Some authors, such as Scherger et al (2017) and Terceño et al (2018), helped us perceive an evolution of research in this period, from modeling to application in case studies.…”
Section: Business Vulnerability Diagnosis: An Integrative Reviewmentioning
confidence: 99%
“…An example of the power of the ordered weighted averaging operators is Kacprzyk and Zaderozny [22] in which, through the choice of the type of the ordered weighted operator and its weights, various voting procedures can be represented, providing a convenient and powerful representation. Also, it has been used to solve different problems [23,24] such as the clustering method for classi ication problems [25] portfolio selection [26], competitiveness [27], econometric forecasting [28], pro it of investment [29], business failure [30], inancial decisions [31], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Business failure occurs when a company is unable to pay its creditors, shareholders and suppliers [1][2][3][4][5]. It is often the consequence of a national economic crisis reflected in some macroeconomic variables, such as high unemployment, declining gross domestic product, declining foreign direct investment and inadequate income distribution [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%